2011
DOI: 10.1093/geronb/gbr071
|View full text |Cite
|
Sign up to set email alerts
|

Age, Criterion Flexibility, and Associative Recognition

Abstract: These results suggest that older adults have preserved metacognitive abilities with regard to assessing the consequences for accuracy of maintaining a lenient criterion when discrimination between experienced and new information becomes more difficult and further suggests that they can take appropriate action to control error rates under these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 28 publications
4
14
1
Order By: Relevance
“…Other studies have reported that older adults are as skilled at flexibly adjusting their criterion placement as younger adults (e.g., Koutstaal, Schacter, Galluccio, & Stofer, 1999). For example, in Pendergrass, Olfman, Schmalstig, Seder, and Light (2012), participants studied a list of word pairs and then received both a difficult test and an easy test. The difficult test list was composed of target pairs and foil pairs where foil pairs were constructed by rearranging studied items.…”
Section: Criterion Flexibility and Ageingmentioning
confidence: 99%
“…Other studies have reported that older adults are as skilled at flexibly adjusting their criterion placement as younger adults (e.g., Koutstaal, Schacter, Galluccio, & Stofer, 1999). For example, in Pendergrass, Olfman, Schmalstig, Seder, and Light (2012), participants studied a list of word pairs and then received both a difficult test and an easy test. The difficult test list was composed of target pairs and foil pairs where foil pairs were constructed by rearranging studied items.…”
Section: Criterion Flexibility and Ageingmentioning
confidence: 99%
“…In contrast, a more conservation response criterion results in a higher likelihood of reporting that a target is absent. Adaptive response criteria have been observed among older adults in memory tasks (Baron & Surdy, 1990; Cassidy & Gutchess, 2015; Marquié & Baracat, 2000; Pendergrass, Olfman, Schmalstig, Seder, & Light, 2012) and auditory perception (Craik, 1969). In driving, adapting response criteria according to the demand and context of the target detection task may benefit older drivers in detecting road hazards.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, this study adds to the growing body of literature demonstrating that older adults can adopt meta-cognitive strategies to improve their recognition performance (Barber & Mather, 2013b;da Silva & Sunderland, 2010;Pendergrass, et al, 2012). We also add to the literature the finding that providing older adults with bogus negative information about their face recognition ability seems to motivate them to employ a more effective recognition strategy, thereby increasing their actual ability to recognize faces.…”
mentioning
confidence: 69%
“…Both older and young adults can adjust their response criterion in relation to task difficulty, with both older and young adults adopting a more conservative response standard as test difficulty increases (Pendergrass, Olfman, Schmalstig, Seder & Light, 2012) and under conditions of stereotype threat (e.g., Barber & Mather, 2013b).…”
mentioning
confidence: 99%